Clinical and public health perspectives of injury admissions for head injury or long bone fracture with hospital codes related to child maltreatment in england 1997–2009. (4th April 2011) - Lee, J; Gonzalez-Izquierdo, A; Ward, A; Gilbert, R
Abstract : Aims: To determine the prevalence of codes related to child maltreatment in hospital administrative records of children with head injury or fracture. Methods: We examined NHS hospital episode statistics for children aged 1 week to 5 years admitted in England 1997–2009) with an intracranial injury (ICI), uncomplicated head injury (no ICI or skull fracture) or a fractured long bone. We determined the prevalence of any maltreatment-related code given type of injury and age group (clinical perspective), and the proportion of any admissions for ICI, uncomplicated head injury or long bone fracture that had a maltreatment-related code (public health perspective). Results: The prevalence of maltreatment-related injury was highest for infants under 6 months with ICI (31%) or long bone fracture (29%) and declined with age. The large majority of maltreatment-related injury admissions occurred in low risk children aged 1 to 5 years with uncomplicated head injury (table 1 ). Conclusions: Under-recording of child maltreatment in hospital administrative data may partly explain the reduced prevalence of maltreatment-related codes with increasing age and is likely to be most marked for uncomplicated head injuries. Clinicians need to take both a clinical and public health perspective. Response to high risk injuries such as ICI and long bone fracture in young infants needs to be combined with a public health approach that recognises that most children with maltreatment-related injury have low risk injuries.